Metacognitive Beliefs Predict Greater Mental Contamination Severity After an Evoking Source - Fergus, Thomas A.; Clayson, Kelsi A.; Dolan, Sara L. (Frontiers in Psychology, 2018)
Mental contamination occurs when individuals experience feelings of internal dirtiness and distress in the absence of physical contact with a contaminant. Women who experience sexual trauma frequently report mental contamination. The self-regulatory executive function (S-REF) model proposes that metacognitive beliefs contribute to the appraisal and regulation of thinking, leading to expectations that metacognitive beliefs would predict greater mental contamination severity following an evoking source. Women who reported directly experiencing sexual trauma (N = 102) completed self-report measures of metacognitive beliefs and covariates during an online study session, and subsequently completed a task that evoked mental contamination during a follow-up in-person study session. Metacognitive beliefs surrounding the uncontrollability and danger of thoughts, cognitive confidence, and the need to control thoughts positively correlated with mental contamination severity following the evoking source. Metacognitive beliefs surrounding the uncontrollability and danger of thoughts predicted greater mental contamination severity following the evoking source in multivariate analyses that statistically controlled for baseline mental contamination severity, trait anxiety, and overlap among the metacognitive beliefs. The present results provide preliminary support for the S-REF model as a potential framework for conceptualizing mental contamination.